Characteristic Flavaglines with Therapeutic Potential for Ischemic Stroke from Aglaia perviridis - Yan-Ping Zhang (432349) (2025)
To investigate the material basis and mechanisms underlying the therapeutic effects of Aglaia perviridis on ischemic stroke, the anti-ischemic stroke activities of various crude extracts and derived compounds were evaluated using both middle cerebral artery occlusion/reperfusion (MCAO/R) rat models and lipopolysaccharide (LPS)-induced BV-2 microglia models. The ethyl acetate extract of A. perviridis (APE), which contains total flavaglines, demonstrated the most significant antineuroinflammatory activity in vitro. Furthermore, APE markedly reduced cerebral infarct volume and alleviated cerebral edema in MCAO/R rats. A comprehensive phytochemical analysis of APE led to the isolation and identification of 16 novel compounds (1a, 1b, 2a, 2b, 3, 4a, 4b, 5a, 5b, 6a, 6b, 7a, 7b, 8a, 8b, and 9) and 10 known analogues (10–19). The flavaglines were characterized using high-performance liquid chromatography (HPLC). The structures of the isolated compounds were elucidated through 1D and 2D nuclear magnetic resonance (NMR), high-resolution electrospray ionization mass spectrometry (HR-ESI-MS), ACD/Structure Elucidator (ACD/SE) analysis, DP4+ probability analysis, and electronic circular dichroism (ECD) calculations. Notably, compounds 1 and 2 were novel valence rearrangement flavanes with a benz[b]furan backbone. Additionally, potential biosynthetic pathways were proposed. In bioassays, compounds 5 and 6 potently inhibited LPS-induced nitric oxide (NO) production in BV-2 cells, with IC50 values of 11.21 ± 3.46 and 2.04 ± 1.10 μM, respectively.